Strategic flexibility choices in the ocean transportation industry. (11th January 2010) - Lagoudis, Ioannis N.; Naim, Mohamed M.; Potter, Andrew T.
Flexibility is an issue widely studied in the manufacturing literature, but only recently has attention been paid to flexibility in logistics and supply chain management. Flexibility is taking prominence due to the uncertainties and disruptions created in the production and distribution processes of an organisation and its respective supply chains. This paper aims at studying the level of transport flexibility achieved in the ocean transportation industry to gain understanding on the strategic choices of carriers to cope with market changes and customer demand. Our analysis indicates the different strategic choices ocean transportation companies need to make with regards to transport flexibility.